Long-Range Proton Channels Constructed via Hierarchical Peptide Self-Assembly - Censor, Semion (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.